ANALISIS STRATEGI PERENCANAAN DAN PENGELOLAAN SDM UKM PARASIKA YANG UNGGUL DAN KOMPETITIF DI ERA DISRUPSI - Dewi, Harnum Kumala; Ramdani, Danny (LP2M Universitas Bina Bangsa, 2025)
The aim of this research is to analyze the planning and management strategies of the Unsika Arts People's Association in facing the era of disruption to obtain superior and competitive human resources, and to find out how the role of the era of disruption or the era of digitalization affects the Parasika work system. The focus of the discussion in this research is the analysis of planning strategies for utilizing the presence of the era of disruption, and planning strategies to face the positive and negative possibilities of the presence of the era of disruption. As well as training strategies and character building to obtain superior and competitive human resources in the era of disruption. The method used in this research is qualitative descriptive research and phenomenological analysis methods. Through the qualitative descriptive method, researchers use data from interviews which are then described descriptively. The informants in this research involved two informants, including the General Chairperson of Parasika, and the Head of the Parasika Human Resources Management Bureau. The second method used in this research is the phenomenological analysis method, which is a type of qualitative research that looks and hears more closely and in detail the individual's explanation and understanding of their experiences. The results of this research show that the planning and human resource management strategy of the Unsika Arts People's Association has a significant impact on developing the quality of human resources in forming superior and competitive students in the era of disruption